Establishment of a COVID‐19 Recovery Unit in a Veterans Affairs Post‐Acute Facility. Issue 10 (11th August 2020) - Sohn, Linda; Lysaght, Marcia; Schwartzman, William A.; Simon, Steven R.; Goetz, Matthew B.; Yoshikawa, Thomas
Abstract : Coronavirus disease 2019 (COVID‐19) is now an epidemic of global proportion, with major adverse impacts on older adults, persons with chronic diseases, and especially residents of long‐term care facilities. This health catastrophe has challenged healthcare facilitiesʼ capacity to deliver care to not only COVID‐19 patients but all patients who need hospital care. We report on a novel approach of utilizing long‐term care beds at a Department of Veterans Affairs healthcare facility for managing recovering COVID‐19 patients. J Am Geriatr Soc 68:2163–2166, 2020.